# System solving 2x-4y = 12    x+3y = 3

justaguide | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

You can use substitution to solve the system of equations

2x - 4y = 12 ...(1)

x + 3y = 3 ...(2)

From (2), x + 3y = 3

=> x = 3 - 3y

Substitute this in (1)

2*(3 - 3y) - 4y = 12

=> 6 - 6y - 4y = 12

=> 6 - 10y...

(The entire section contains 2 answers and 112 words.)

check Approved by eNotes Editorial

pohnpei397 | Certified Educator

calendarEducator since 2009

starTop subjects are History, Literature, and Social Sciences

check Approved by eNotes Editorial

giorgiana1976 | Student

We'll solve the system using elimination method.

We'll multiply the 1st equation by 3:

6x - 12y = 36 (3)

We'll multiply the 2nd equation by 4:

4x + 12y = 12 (4)

6x - 12y + 4x + 12y  = 36 + 12

We'll combine and eliminate like terms:

10x = 48

x = 4.8

We'll substitute x in the 2nd equation:

4.8 + 3y = 3

3y = 3 - 4.8

3y = -1.8

y = -1.8/3

y = -0.6

The solution of the system is the pair (4.8 ; -0.6).

check Approved by eNotes Editorial